KECEMASAN MATEMATIS SEBAGAI FAKTOR YANG MEMPENGARUHI KEMAMPUAN PEMECAHAN MASALAH SISWA SMP: KAJIAN LITERATUR SISTEMATIS - Meileni, Dita; Heni Pujiastuti; Nurul Anriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low problem‑solving performance among middle schoolers is often linked to math anxiety, which disrupts focus and strategy use. This study systematically reviews the effect of math anxiety on middle‑school students’ problem‑solving ability. Method: a PRISMA‑guided systematic literature review of national databases (Google Scholar, Garuda) with inclusion criteria of junior‑high samples, math‑anxiety problem‑solving variables, and publications from 2019–2026. Eligible studies were extracted for sample characteristics, instruments, task types, and main findings, and synthesized thematically. Results show a consistent negative association: higher anxiety corresponds to lower performance across Polya’s stages; effects are stronger on non‑routine tasks and geometry topics. Pedagogical approaches Realistic Mathematics Education, open‑ended problems, and Problem‑Based Learning tend to reduce anxiety while improving performance. Embedding anxiety management into lesson design via emotion‑regulation supports, procedural scaffolds, and context‑rich tasks is recommended; future research should adopt longitudinal/experimental designs with standardized measures.